STUDI KOMPARATIF TINGKAT KEPUASAN DALAM MEMBACA KORAN HARIAN TRIBUN BALI DAN PORTAL BERITA BALI.TRIBUNNEWS.COM PADA MASYARAKAT KOTA DENPASAR - Juhendri, Arif; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT Daily Tribune Bali and Bali.tribunnews.com experienced media convergence. This research aims to know the motives and satisfaction. Denpasar is recorded as the most used nternet and the most media consumption in Bali. The pattern of media consumption that is a reference is the1motive by McQuail. The theory is the Uses and Gratifications theory. Using qualitative methods of descriptive. Sampling techniques are purposive1sampling. Data obtained by spreading the questionnaire Likert1scale. Analytical techniques are descriptive statistics with the average1score of1motives and satisfaction. The results of the study there are no motives1that are satisfied1with reading Daily Tribune Bali. Then only one motive is able to be satisfied in reading the news portal Bali.tribunnews.com is an entertainment motif. So the result of this1research shows the daily reader of Tribune Bali or Bali.tribunnews.com news Portal can,t be said as a fairly effective medium to give satisfaction. Keyword: Community,Denpasar, Motive, Satisfaction, Society, Tribun